2017
DOI: 10.2147/rmhp.s138300
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of counseling practice in medicine retail outlets in Mekelle City, Northern Ethiopia

Abstract: IntroductionPatient counseling can ideally be providing medication information orally or in written form to patients or their attendants, and it helps to form a concordant approach on encouraging patient involvement in the pharmaceutical care process and to explore patient’s knowledge and understanding. Lack of adequate knowledge on drugs and up-to-date drug information are the major factor that hinders counseling services. This study assessed counseling practice of pharmacy professionals in Mekelle City.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 7 publications
5
12
0
Order By: Relevance
“…The current study was an observational study similar to study conducted in Bahir Dar city, 7 and the study in Mekele was conducted using self-administered questionnaires, with data collected as claimed by pharmacy professionals. 16 This study revealed that 90% of participants stated that they always tell what to do if a patient misses a dose, whereas reports from Bahir Dar and Mekele cities revealed 7.8% and 13%, respectively. 5 This disparity could be explained by contextual differences in the study settings and populations studied in the two research.…”
Section: Discussionmentioning
confidence: 79%
“…The current study was an observational study similar to study conducted in Bahir Dar city, 7 and the study in Mekele was conducted using self-administered questionnaires, with data collected as claimed by pharmacy professionals. 16 This study revealed that 90% of participants stated that they always tell what to do if a patient misses a dose, whereas reports from Bahir Dar and Mekele cities revealed 7.8% and 13%, respectively. 5 This disparity could be explained by contextual differences in the study settings and populations studied in the two research.…”
Section: Discussionmentioning
confidence: 79%
“… 5 Hirko N, Edessa D, SisayM 20 Perceived poor communication (7.1%), not clear ascent of the dispenser (12.8%), impoliteness of the dispenser (6.4%), non-clarity of the dispenser’s guidance (9.2%) and insufficiency of the dispenser’ information (27.3%) 6 Hirko N, EdessaD 5 Clearness of pharmacist’s voice and tone (16.6%), impoliteness of service provider (5.90%), non-clarity of the pharmacist’s instruction to patient (8.8%) and insufficiency of pharmacist’s knowledge (11.6%) 7 TayeY 22 Pharmacists‘ communication skills (β= 0.44), pharmacists’ empathy (β= 0.07), provision of instruction on usage of medicines (β= 0.15) and provision of information on disease condition (β= 0.23) were determinants of satisfactory counseling. 8 Wabe NT, Raju N, Angamo MT 23 Lack of knowledge (43.8%) 9 Ali S, Shimels T, Bilal AI 24 Lack of updated drug information (91.5%) Educational qualification, knowledge and age had significant influence on counseling response (P<0.05) 10 Gelayee DA, Birara MK 26 Lack of knowledge of practitioners (80.96%), lack of time of practitioners (7.94%) and lack of interest of practitioners (7.94%) 11 Belay et al 27 Lack of knowledge of practitioners (37%), lack of updated drug information (49%), poor communication (52%), lack of confidence (25%), lack of interest (30%), lack of experience (30%), poor attitude (25%) and not considering it as part of professional duties (26%) …”
Section: Resultsmentioning
confidence: 99%
“… 3 Surur et al 18 High patient load (29.5%) 4 Nigussie S and EdessaD 19 Suitability of dispensing area (62.5%), privacy in dispensing area (41.2%), waiting time for service (74.6%), availability of prescribed drug (38.9) and location of outpatient pharmacy (62%), lack of quality system (AOR=13.56) were determinants of dissatisfaction. 5 Hirko N, Edessa D, SisayM 20 Non-suitable waiting area (17.3%) 6 Hirko N, EdessaD 5 Not comfortable waiting area (9.7%) 7 Wabe NT, Raju N, Angamo MT 23 High patient load (29.7%) and no legalization (25%) 8 Ali S, Shimels T, Bilal AI 24 Lack of space (21.4%), high patient load (23.8%) and no legalization (12%) 9 Gelayee DA, Birara MK 26 Absence or inadequacy of counseling guidelines (3.17%) 10 Belay et al 27 High patient load (62%) and absence of private counseling room (51%) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations